2017
DOI: 10.4236/ojapps.2017.75019
|View full text |Cite
|
Sign up to set email alerts
|

Role of Canal Lining on Groundwater Fluctuations: A Modeling Simulation Approach for Jaalwala Distributary, Bahawalnagar

Abstract: Jaalwala Distributary was selected to see the consequences of concrete lining on the underlying saline groundwater table. Its middle and tail portions were concrete lined whereas the head portion was still unlined. Visual MODFLOW 2011.1 was used to simulate the effects of concrete lining on saline groundwater in two-dimensional format. Simulation results showed a gradual rise of electrical conductivity (EC) up to 7000 µS/cm and decline in water table depth to nine feet (2.74 m). It observed negligible inflows … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Khan et al [20] observed a gradual rise in electrical conductivity (EC), using Visual MODFLOW to simulate the effects of a concrete lining on groundwater. Lesser et al [21] determined the effect of lining canals on groundwater levels in the Mexicali Valley.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al [20] observed a gradual rise in electrical conductivity (EC), using Visual MODFLOW to simulate the effects of a concrete lining on groundwater. Lesser et al [21] determined the effect of lining canals on groundwater levels in the Mexicali Valley.…”
Section: Introductionmentioning
confidence: 99%